Sociodemographic variations in organic food consumption and food choice motives among malaysian adults: a study between organic and non-organic food consumers - Jaafar, Nur Aqilah Amalina; Sulaiman, Norhasmah; Zainal Badari, Shamsul Azahari; Sabran, Mohd Redzwan (Human Resources Management Academic Research Society (HRMARS), 2024)
The growing trend of organic food consumption worldwide highlights its importance regarding sustainability, environmental impact, the food system, and ethical considerations. This study aims to identify differences between organic and non-organic food consumers regarding their sociodemographic characteristics and food choice motives to better understand this trend. Through an online survey using six targeted Facebook advertisements across six zones in Malaysia, 424 Malaysian adults were sampled. The results revealed that organic food consumers had higher monthly incomes, were more likely to be married, and included a higher percentage of Bumiputera. In terms of food choice motivations, the top three priorities for organic food consumers were health, mood, food safety, and nutrition. In comparison, non-organic food consumers were more motivated by price, sensory appeal, and convenience. These findings suggest the need for different strategies to promote organic food consumption among adults in developing nations, considering their specific sociodemographic characteristics and food choice motives.